Procedural efficiency of the statements obtained in collaboration procedures - Fernández López, Mercedes (2018)
In this article the author develops the procedural treatment that receives the information obtained through collaborators in the framework of the investigation of crimes committed by criminal organizations. Thus, the different collaboration formulas and the conditions required for the former to become effective as evidence in the process will be presented and analyzed; all the above taking into account the necessary harmony with the principles that govern the prosecution of criminal cases.